Pengembangan Produk Flakes Cereal Berbasis Tepung Porang dan Beras Merah sebagai Alternatif Sarapan Tinggi Serat - Mila Putri Apriliana; Rosyda Dianah (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
Breakfast habits in adults are important for maintaining nutritional balance because they provide the body with its initial energy. Consuming high fiber foods for breakfast can increase satiety, maintain stable blood sugar levels, and support digestive health. Cereal flakes are a convenient food product that is easy to serve as a breakfast option. This study aimed to develop cereal flakes made from porang flour and brown rice using a Completely Randomized Design (CRD) with three treatments F1(60% ; 40%), F2 (50% : 50%) dan  F3 (40% : 60%). A hedonic test involving 63 semi trained panelists was conducted. The study was conducted at the IPB Vocational School. Data analysis was performed using SPSS 31.0 with the Kruskal-Wallis test. The results of the hedonic test indicated that the best formula was F3, with a composition of 40 g of porang flour and 60 g of red rice flour. This formula has an energy content of 498 kcal/100 g, 4% protein, 22% fat, 70% carbohydrates, and 21.4% dietary fiber. This dietary fiber content is categorized as high, in accordance with the criteria for high-fiber foods.